Factores protectores de estrés psicosocial de la Policía Municipal De Puerto Vallarta - López Solorio, José Adolfo (Archivos de criminología, seguridad privada y criminalística, 2023)
This article presents part of the results of a investigation that was developed by applying the provisions of NOM-035 (Official Mexican Standard) regarding "psychosocial risk factors in work environments" in a municipal police force in Jalisco, Mexico. The results obtained contribute to the understanding of the phenomenon of stress within police groups at the same time that a sociodemographic context of increasing violence and poor citizen perception develops. Part of the relevant results show the existence of a protective factor for stress management, the sense of belonging. Result coinciding with that found by other investigations.